2021
DOI: 10.1136/bmjdrc-2021-002148
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antidiabetic treatment and impaired hypoglycemia awareness in type 2 diabetes mellitus assessed in Spanish community pharmacies: the ADHIFAC study

Abstract: IntroductionAdherence to treatment and hypoglycemia awareness are strongly linked to glycemic control and hypoglycemia risk in people with type 2 diabetes mellitus (T2DM). Community pharmacies are suitable facilities to detect these conditions, and should be involved in the strategies to minimize the associated risks and burden.Research design and methodsThis cross-sectional study conducted at community pharmacies across Spain assessed the prevalence of low adherence to antidiabetic treatments, the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…In Asia, the prevalence of IAH determined by the Gold and Clarke questionnaires among people with insulin-treated type 2 diabetes collected from hospitals was 19.6% and 13.7%, respectively, in Singapore, but that from clinics was between 5.93% and 17.01% in Jordan. 11,12 Among people with insulinand oral antihyperglycemic-treated type 2 diabetes, the prevalence of IAH based on the Clarke questionnaire was 25% in Spain 15 and 52.1% in the Kingdom of Saudi Arabia. 23 All of these studies showed that IAH prevalence was higher among patients treated with insulin, with or without oral antihyperglycemic agents, than among those treated with insulin only.…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, the prevalence of IAH determined by the Gold and Clarke questionnaires among people with insulin-treated type 2 diabetes collected from hospitals was 19.6% and 13.7%, respectively, in Singapore, but that from clinics was between 5.93% and 17.01% in Jordan. 11,12 Among people with insulinand oral antihyperglycemic-treated type 2 diabetes, the prevalence of IAH based on the Clarke questionnaire was 25% in Spain 15 and 52.1% in the Kingdom of Saudi Arabia. 23 All of these studies showed that IAH prevalence was higher among patients treated with insulin, with or without oral antihyperglycemic agents, than among those treated with insulin only.…”
Section: Findings In Contextmentioning
confidence: 99%
“…The factors associated with IAH in type 2 diabetes included lower education, 15 nonpartnered status, 13 high body mass index, 13 diabetes-related comorbidities, 15 lower medication adherence, 15,16 use of complex insulin regimens, 13 higher frequency of hypoglycemia in the past 6 months, and severe hypoglycemia events in the past year. 12 Oral antihyperglycemic agents, especially sulfonylureas, carry high risk for hypoglycemia with long-term use.…”
Section: Introductionmentioning
confidence: 99%